2005
DOI: 10.1007/s11010-005-6933-0
|View full text |Cite
|
Sign up to set email alerts
|

Glycation-induced inactivation of aspartate aminotransferase, effect of uric acid

Abstract: Glycation is common posttranslational modification of proteins impairing their function, which occurs during diabetes mellitus and aging. Beside extracellular glycation of long-lived proteins, intracellular modifications of short-lived proteins by more reactive sugars like fructose are possible. The process includes free oxygen radicals (glycoxidation). In an attempt to reduce glycoxidation and formation of advanced glycation products (AGE), influence of 0.2-1.2 mM uric acid as endogenous antioxidant on glycox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Several proteins namely hemoglobin [14][15][16], crystallins [33], glyceraldehydes 3-phosphate dehydrogenase, catalase, superoxide dismutase [34], albumin [35] and aspartate amino transferase [36] have been reported to be the targets of fructose modification. Although glycation of Mb has been reported from our laboratory [8,9], there has been no study on its fructation.…”
Section: Resultsmentioning
confidence: 99%
“…Several proteins namely hemoglobin [14][15][16], crystallins [33], glyceraldehydes 3-phosphate dehydrogenase, catalase, superoxide dismutase [34], albumin [35] and aspartate amino transferase [36] have been reported to be the targets of fructose modification. Although glycation of Mb has been reported from our laboratory [8,9], there has been no study on its fructation.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species (ROS) such as O 2 •− , H 2 O 2 , and • OH may contribute to these reactions, which require trace levels of catalytic redox-active transition metal ions. The process includes also oxidative steps and is therefore called glycoxidation [6][7][8]. Regarding the significance of glycoxidative stress to diabetic pathology, a supplement of antioxidants to inhibit the process of protein modification appears to be a good strategy for preventing diabetic complications [9].…”
Section: Introductionmentioning
confidence: 99%
“…The aspartate aminotransferase was reported to be associated with glucose metabolism and insulin resistance [38]. Bousova et al reported reduced aspartate amino transferase activity induced by fructose and the resulting glycation in vitro and observed beneficial effects of uric acid in that context [55]. Hageman et al reported that feeding an aspartate rich protein blend decreased the postprandial glucose response in rats [56].…”
Section: Discussionmentioning
confidence: 99%